Human Amniotic Membrane: A review on tissue engineering, application, and storage. Issue 8 (14th December 2020) - Leal‐Marin, Sara; Kern, Thomas; Hofmann, Nicola; Pogozhykh, Olena; Framme, Carsten; Börgel, Martin; Figueiredo, Constanca; Glasmacher, Birgit; Gryshkov, Oleksandr
Abstract: Human amniotic membrane (hAM) has been employed as scaffolding material in a wide range of tissue engineering applications, especially as a skin dressing and as a graft for corneal treatment, due to the structure of the extracellular matrix and excellent biological properties that enhance both wound healing and tissue regeneration. This review highlights recent work and current knowledge on the application of native hAM, and/or production of hAM‐based tissue‐engineered products to create scaffolds mimicking the structure of the native membrane to enhance the hAM performance. Moreover, an overview is presented on the available (cryo) preservation techniques for storage of native hAM and tissue‐engineered products that are necessary to maintain biological functions such as angiogenesis, anti‐inflammation, antifibrotic and antibacterial activity.